Dongeng Masyarakat Kelurahan Telayap Kecamatan Pelalawan Kabupaten Pelalawan Provinsi Riau dalam Kajian Sastra Ekologis - Andriyani, Noni; Alber, Alber (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2019)
This research was conducted base on two interests, the interests of protecting culture especially local wisdom and the interests of protecting the environment. The importance of preserving culture, especially local wisdom, is in the effort to document fairy tales in Telayap Village, Pelalawan District, Pelalawan Regency, Riau Province. Moreover, the importance of protecting the environment is also in the effort to examine the tales that will be obtained with ecological literary theory. The community of Telayap Village, Pelalawan District, Pelalawan Regency, Riau Province has not been well documented and is assumed to have a lot of environmental content. Therefore, this research was a form of manifestation of preserving local culture and preserving the environment at the same time. Fairy tales need good documentation so that they are not extinct or not recognized as belonging to other nations. Behind their simple form, fairy tales can actually teach many good things to shape one's character, including shaping environmental character. This ecological literary theory tries to answer the relationship of literature with its environment. Not many people have done research with this theory. Meanwhile, the discussion on the environment at this time is an important agenda to heighten the degradation of public awareness in protecting and preserving the environment. This also shows that this research has implications for character in education. The formulation of the problem in this study were: (1) What are the fables contained in the Telayap Kelurahan community, Pelalawan District, Pelalawan Regency, Riau? and (2) What is the ecological literature in the fairy tales of the Telayap Village, Pelalawan District, Pelalawan Regency, Riau? The theory used to study ecological literature is Garrard's theory (in Endraswara, 2016) regarding the six concepts of ecological literature which include (1) pollution; (2) wilderness; (3) disaster; (4) housing / residence; (5) animals; and (6) earth. This study uses a qualitative approach with ethnographic methods. The research located in Telayap Village, Pelalawan District, Pelalawan Regency, Riau Province. Research data sources were informants selected based on qualitative research informant determination techniques. Data collection techniques included observation techniques, recording techniques, conversational skills, and collaboration techniques. Data analysis techniques are based on Miles and Huberman's interactive techniques. The results of this study indicated that the tales of the Telayap community contain the whole concept of ecological literature according to Garrard. The concept includes pollution, wilderness, disaster, housing/ shelter, animals, and the earth. The concept that often arises is the concept of housing/shelter, animals, and earth and the least is the concept of disaster.